Determination of Dehydrogenase Activities Involved in D-Glucose Oxidation in Gluconobacter and Acetobacter Strains - Sainz, Florencia; Jesús Torija, María; Matsutani, Minenosuke; Kataoka, Naoya; Yakushi, Toshiharu; Matsushita, Kazunobu; Mas, Albert (Frontiers in Microbiology, 2016)
Acetic acid bacteria (AAB) are known for rapid and incomplete oxidation of an extensively variety of alcohols and carbohydrates, resulting in the accumulation of organic acids as the final products. These oxidative fermentations in AAB are catalyzed by PQQ- or FAD- dependent membrane bound dehydrogenases. In the present study, the enzyme activity of the membrane bound dehydrogenases (membrane-bound PQQ-glucose dehydrogenase (mGDH), D-gluconate dehydrogenase (GADH) and membrane-bound glycerol dehydrogenase (GLDH)) involved in the oxidation of D-glucose and D-gluconic acid (GA) was determined in six strains of three different species of AAB (three natural and three type strains). Moreover, the effect of these activities on the production of related metabolites (GA, 2-keto-D-gluconic acid (2KGA) and 5-keto-D-gluconic acid (5KGA)) was analyzed. The natural strains belonging to Gluconobacter showed a high mGDH activity and low activity in GADH and GLDH, whereas the A. malorum strain presented low activity in the three enzymes. Nevertheless, no correlation was observed between the activity of these enzymes and the concentration of the corresponding metabolites. In fact, all the tested strains were able to oxidize D-glucose to GA, being maximal at the late exponential phase of the AAB growth (24 h), which coincided with glucose exhaustion and the maximum mGDH activity. Instead, only some of the tested strains were capable of producing 2KGA and/or 5KGA. In the case of G. oxydans strains, no 2KGA production was detected which is related to the absence of GADH activity after 24 h, while in the remaining strains, detection of GADH activity after 24h resulted in a high accumulation of 2KGA. Therefore, it is possible to choose the best strain depending on the desired product composition. Moreover, the sequences of these genes were used to construct phylogenetic trees. According to the sequence of gcd, gene coding for mGDH, Acetobacter and Komagataeibacter were phylogenetically more closely related each other than with Gluconobacter.